2022
DOI: 10.3389/fmicb.2022.813415
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Use of Rhizobacteria and Moringa Leaf Extract Mitigates the Adverse Effects of Drought Stress in Wheat (Triticum aestivum L.)

Abstract: Less nutrient availability and drought stress are some serious concerns of agriculture. Both biotic and abiotic stress factors have the potential to limit crop productivity. However, several organic extracts obtained from moringa leaves may induce immunity in plants under nutritional and drought stress for increasing their survival. Additionally, some rhizobacterial strains have the ability to enhance root growth for better nutrient and water uptake in stress conditions. To cover the knowledge gap on the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…Abdelaal and colleagues [ 20 ] showed similar results with proline on barley. These results are in agreement with those obtained by Lalarukh et al [ 9 ], who showed that winter wheat inoculated with Pseudomonas aeruginosa and Azeem et al [ 37 ], who showed that maize plants treated with Bacillus strains reduced the formation of H 2 O 2 under drought stress in comparison to uninoculated control plants. Our results showed that the addition of Ca to the soil has a positive effect on protecting winter wheat cells from oxidative damage.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Abdelaal and colleagues [ 20 ] showed similar results with proline on barley. These results are in agreement with those obtained by Lalarukh et al [ 9 ], who showed that winter wheat inoculated with Pseudomonas aeruginosa and Azeem et al [ 37 ], who showed that maize plants treated with Bacillus strains reduced the formation of H 2 O 2 under drought stress in comparison to uninoculated control plants. Our results showed that the addition of Ca to the soil has a positive effect on protecting winter wheat cells from oxidative damage.…”
Section: Discussionsupporting
confidence: 93%
“…We found data about the positive effect of exogenous calcium [ 30 , 35 ] and plant microbial probiotics application on the chlorophyll content of wheat seedlings exposed to drought. It was reported that Burkholderia phytofirmans , Bacillus megaterium and Bacillus licheniformis , Pseudomonas aeruginosa significantly improve chlorophyll content under drought stress conditions [ 9 , 36 , 37 ]. Our study showed that the application of microbial probiotic preparation ProbioHumus and Ca increased the total content of chlorophyll under drought conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this nutrient is highly mobile in plant and acts directly in regulating the osmotic potential in compartments to increase their turgor 46 . Generally, the nutrient imbalance that occurred in drought-stressed plants may led to undesirable drop in plant pigments (chlorophyll A, chloro B, total chlorophyll and carotenoids) and photo-assimilates 16 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Biochar is another promising additive that can mitigate the adverse effects of drought on plant growth and productivity, e.g., sorghum 14 , maize 15 and wheat 2 , 16 . This might take place via (I) increasing soil water retention, hence reducing soil irrigation demands 17 , (II) increasing nutrient use efficiency 18 , (III) stimulating auxin, gibberellin and brassinosteroids regulation 19 and (IV) increasing plant chlorophyll content 20 , stomatal conductance, cytotoxicity and leaf K + content 21 .…”
Section: Introductionmentioning
confidence: 99%